2020
DOI: 10.46989/001c.21168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Proanthocyanidins Supplementation on Growth Performance, Digestive Enzymes Activities and Microbiota in the Intestine of Juvenile American Eels (Anguilla rostrata) Cultured in Cement Tanks

Abstract: This trial was conducted to investigate the effects of proanthocyanidins (PACs) on the growth performance, digestive enzymes activities and microbiota in the intestines of juvenile American eels (Anguilla rostrata) cultured in cement tanks. Six cement tanks stocked with similar fish size and weight (about 120 g/fish and 2116 kg/tank) were randomly divided into a control group fed with a commercial diet and a PACs group fed with a commercial diet supplemented 400 mg/kg PACs, with three replicates in each group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…In the present study, juvenile American eels of CAs group had a lower abundance of Firmicutes compared with the control group. Firmicutes was the main phyla in many fish species, but some of these bacteria could cause the lower growth rate of European eel (Shi et al, 2020;Wang et al, 2020). These results indicated that CAs might increase the abundance of beneficial microbiota at the phylum level related to nutrient digestion and absorption.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In the present study, juvenile American eels of CAs group had a lower abundance of Firmicutes compared with the control group. Firmicutes was the main phyla in many fish species, but some of these bacteria could cause the lower growth rate of European eel (Shi et al, 2020;Wang et al, 2020). These results indicated that CAs might increase the abundance of beneficial microbiota at the phylum level related to nutrient digestion and absorption.…”
Section: Discussionmentioning
confidence: 94%
“…The microbiota plays an important role in the development of normal intestinal function, stimulation of the innate immune response, and maintenance of the balance of the intestinal environment (Wang et al, 2020). Alpha diversity could reflect the richness and diversity of microbial communities, mainly including indexes of Chao1, Shannon and Simpson (Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eels, reputed as “ginseng in water”, are one of the most common fish species cultured around the world, and they play an important role in international trade [ 14 ]. The American eel has become the main cultured eel species in Asia since European eels ( Anguilla anguilla ) have been listed as extremely endangered species [ 14 , 15 ]. The purpose of the present study was to investigate the effects of dietary supplementation of PSPc on the growth performance and lipid metabolism of juvenile American eels.…”
Section: Introductionmentioning
confidence: 99%